CRF serum levels differentiate PTSD from healthy controls and TBI in military veterans. Issue 4 (28th June 2021) - Ramos‐Cejudo, Jaime; Genfi, Afia; Abu‐Amara, Duna; Debure, Ludovic; Qian, Meng; Laska, Eugene; Siegel, Carole; Milton, Nicholas; Newman, Jennifer; Blessing, Esther; Li, Meng; Etkin, Amit; et al.
Abstract : Background and Objective: Posttraumatic stress disorder (PTSD) is a serious and frequently debilitating psychiatric condition that can occur in people who have experienced traumatic stressors, such as war, violence, sexual assault and other life‐threatening events. Treatment of PTSD and traumatic brain injury (TBI) in veterans is challenged by diagnostic complexity, partially due to PTSD and TBI symptoms overlap and to the fact that subjective self‐report assessments may be influenced by a patient's willingness to share their traumatic experiences and resulting symptoms. Corticotropin‐releasing factor (CRF) is one of the main mediators of hypothalamic pituitary adrenal (HPA)‐axis responses in stress and anxiety. Methods and Results: We analyzed serum CRF levels in 230 participants including heathy controls (64), and individuals with PTSD (53), TBI (70) or PTSD + TBI (43) by enzyme immunoassay (EIA). Significantly lower CRF levels were found in both the PTSD and PTSD + TBI groups compared to healthy control (PTSD vs. Controls: P = 0.0014, PTSD + TBI vs. Controls: P = 0.0011) and chronic TBI participants (PTSD vs. TBI: P < 0.0001, PTSD + TBI vs. TBI: P < 0.0001), suggesting a PTSD‐related mechanism independent from TBI and associated with CRF reduction. CRF levels negatively correlated with PTSD severity on the Clinically Administered PTSD Scale (CAPS‐5) scale in the whole study group. Conclusions: Hyperactivation of the HPA axis has been classically identified in acute stress. However, the recognized enhanced feedback inhibition of the HPA axis in chronic stress supports our findings of lower CRF in PTSD patients. This study suggests that reduced serum CRF in PTSD should be further investigated. Future validation studies will establish if CRF is a possible blood biomarker for PTSD and/or for differentiating PTSD and chronic TBI symptomatology. highlights: The HPA axis is activated under acute stress conditions, but an enhanced feedback inhibition may be prevalent in chronic stress conditions such as PTSD. We observed a reduction in serum CRF levels in veterans with PTSD and PTSD + TBI, but not in veterans with chronic TBI alone. A serum CRF reduction may be indicative of CNS mechanisms specific to PTSD and should be further evaluated as a possible peripheral biomarker.